PENGEMBANGAN MEDIA INFUS WATER DALAM PEMBELAJARAN EKSPERIMEN-SAINS ANAK USIA DINI DI RA BAHRUL ULUM ZAIDAH WAJAK-MALANG - Waffi, Helen Vivi Qowiyul; Yulia, Nikmahtul Khoir Tri (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2025)
Learning about medicinal plants/toga is explored through the water infusion technique. The purpose of this study is to describe the form of media, materials and results of the development of Infused water media for experimental-science learning for early childhood. This study uses the Research and Development (R&D) method with the Borg and Gall model approach using data collection techniques including observation results, media expert instruments, material expert instruments, large group trials, small group trials, and documentation. Infused water media is designed as an interactive learning medium that combines the concepts of health, creativity, and practical experiments. The results show that children are involved in the process of selecting, mixing, and observing natural ingredients to produce infused water products that are suitable for consumption and have educational value. The actualization of the